Agonism activities of lyso-phosphatidylcholines (LPC) Ligands binding to peroxisome proliferator-activated receptor gamma (PPARγ). Issue 2 (22nd January 2020) - Wang, Jiayue; Wang, Bohong; Zhang, Yan
Abstract: PPARγ is an isoform of peroxisome proliferator-activated receptor (PPAR) belonging to a super family of nuclear receptors and is a primary target of the effective drug to treat the type II diabetes. The experiments found that Lyso-phosphatidylcholines (LPC) could bind to PPARγ, but the binding modes remain unknown. We used the Molecular Docking and Molecular Dynamic (MD) simulations to study the binding of four LPC ligands (LPC16:0, LPC18:0, LPC18:1-1 and LPC18:1-2) to PPARγ. The two-step MD simulations were employed to determine the final binding modes. The 20 ns MD simulations for four final LPC-PPARγ complexes were performed to analyze their structures, the binding key residues, and agonism activities. The results reveal that three LPC ligands (LPC16:0, LPC18:0 and LPC18:1-1) bind to Arm II and III regions of the Ligand Binding Domain (LBD) pocket, whereas they do not interact with Tyr473 of Helix 12 (H12). In contrast, LPC18:1-2 can form the hydrogen bonds with Tyr473 and bind into Arm I and II regions. Comparing with the paradigm systems of the full agonist (Rosiglitazone–PPARγ) and the partial agonist (MRL24–PPARγ), our results indicate that LPC16:0, LPC18:0 and LPC18:1-1 could be the potential partial agonists and LPC18:1-2 could be a full agonist. The in-depth analysis of the residue fluctuations and structure alignment confirm the present prediction of the LPC agonism activities. Communicated by Ramaswamy H. Sarma